2008
DOI: 10.1159/000156916
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical Treatment of Intracanalicular Vestibular Schwannomas

Abstract: Early treatment of intracanalicular vestibular schwannomas (IVSs) may be advisable because their spontaneous course will show hearing loss in most cases. Advanced microsurgical techniques and continuous intraoperative monitoring of cranial nerves may allow hearing preservation (HP) without facial nerve damage. However, there are still controversies about the definition of HP and the best surgical approach that should be used. In this study, we reviewed the main data from the recent literature on IVS surgery an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Further comparison of surgical treatment effectiveness showed that the group who had conservative treatment after the first surgery preserved more auditory nerves than the nonsurgical treatment group, whereas no significant differences in facial and posterior cranial nerve retention were observed in this study. Similarly, a meta-analysis performed by Noudel et al (22) showed that the suboccipital sigmoid sinus approach is superior to the facial and auditory neuroprotection. Since the suboccipital retrosigmoid approach can not directly expose the internal auditory canal, the posterior wall of the internal auditory canal should be removed to expose the base of the internal auditory canal to the tumors invading the internal auditory canal, which can easily damage the posterior semicircular canal and facial nerve.…”
Section: Discussionmentioning
confidence: 88%
“…Further comparison of surgical treatment effectiveness showed that the group who had conservative treatment after the first surgery preserved more auditory nerves than the nonsurgical treatment group, whereas no significant differences in facial and posterior cranial nerve retention were observed in this study. Similarly, a meta-analysis performed by Noudel et al (22) showed that the suboccipital sigmoid sinus approach is superior to the facial and auditory neuroprotection. Since the suboccipital retrosigmoid approach can not directly expose the internal auditory canal, the posterior wall of the internal auditory canal should be removed to expose the base of the internal auditory canal to the tumors invading the internal auditory canal, which can easily damage the posterior semicircular canal and facial nerve.…”
Section: Discussionmentioning
confidence: 88%